One Year Survey of Human Rotavirus Strains Suggests the Emergence of Genotype G12 in Cameroon. Issue 8 (13th June 2013) - Ndze, Valentine N.; Papp, Hajnalka; Achidi, Eric A.; Gonsu, Kamga H.; László, Brigitta; Farkas, Szilvia; Kisfali, Péter; Melegh, Béla; Esona, Mathew D.; Bowen, Michael D.; Bányai, K.; Gentsch, Jon R.; et al.
Abstract In this study the emergence of rotavirus A genotype G12 in children <5 years of age is reported from Cameroon during 2010/2011. A total of 135 human stool samples were P and G genotyped by reverse transcriptase PCR. Six different rotavirus VP7 genotypes were detected, including G1, G2, G3, G8, G9, and G12 in combinations with P[4], P[6] and P[8] VP4 genotypes. Genotype G12 predominated in combination with P[8] (54.1%) and P[6] (10.4%) genotypes followed by G1P[6] (8.2%), G3P[6] (6.7%), G2P[4] (5.9%), G8P[6] (3.7%), G2P[6] (0.7%), G3P[8] (0.7%), and G9P[8] (0.7%). Genotype P[6] strains in combination with various G‐types represented a substantial proportion (N = 44, 32.6%) of the genotyped strains. Partially typed strains included G12P[NT] (2.2%); G3P[NT] (0.7%); G(NT)P[6] (1.5%); and G(NT)P[8] (0.7%). Mixed infections were found in five specimens (3.7%) in several combinations including G1 + G12P[6], G2 + G3P[6] + P[8], G3 + G8P[6], G3 + G12P[6] + P[8], and G12P[6] + P[8]. The approximately 10% relative frequency of G12P[6] strains detected in this study suggests that this strain is emerging in Cameroon and should be monitored carefully as rotavirus vaccine is implemented in this country, as it shares neither G‐ nor P‐type specificity with strains in the RotaTeq® and Rotarix® vaccines. These findings are consistent with other recent reports of the global spread and increasing epidemiologic importance of G12 and P[6] strains. J. Med. Virol. 85:1485–1490, 2013. © 2013 Wiley Periodicals, Inc.